Update Breast Cancer 2021 Part 2-Advanced Stages, Long-Term Consequences and Biomarkers - Ditsch, Nina; Stickeler, Elmar; Behrens, Annika; Belleville, Erik; Fasching, Peter; Fehm, Tanja N.; Hartkopf, Andreas D.; Jackisch, Christian; Janni, Wolfgang; Kolberg-Liedtke, Cornelia; Kolberg, Hans-Christian; Lueftner, Diana; et al. (Geburtshilfe und Frauenheilkunde, 2021)
This review summarises and discusses significant aspects of recently published studies on patient treatment in advanced breast cancer and on biomarkers in breast cancer. In recent years, a large number of drugs for all molecular subtypes have been developed up to phase III trials. With regard to immune checkpoint inhibitors in metastasised breast cancer, the recent discussion has centred on the best candidate for combined chemotherapy. The oral taxanes could become a new type of oral chemotherapies. There is a growing body of data on biomarkers for the use of CDK4/6 inhibitors, which could also signify further development for other molecular subtypes. New substances have been developed for metastatic HER2+ breast cancer that still result in good remission even after massive prior treatment and/or cerebral metastasis. Similarly, knowledge is growing about targeted therapies with antibody-drug conjugates (ADC) against Trop-2, which could bolster our therapeutic armoury in triple-negative breast cancer (TNBC). In addition, the clinical focus is on understanding how to maintain fertility after breast cancer treatment. Here, pooled analyses provide new insights.
CRIS-Team WoS Importer:2021-05-21